Bartonian orthophragminids from the Fulra Limestone (Kutch, W India) and coeval units in Sulaiman Range, Pakistan: a synthesis of shallow benthic zone (SBZ) 17 for the Indian Subcontinent. Issue 1 (1st January 2018) - Özcan, Ercan; Saraswati, Pratul Kumar; Yücel, Ali Osman; Ali, Nowrad; Hanif, Muhammad
Abstract: Orthophragminids from the Bartonian Fulra Limestone in Kutch, India and the coeval units in Sulaiman Range in Pakistan suggest the establishment of a significant number of endemic species in the Indian subcontinent (Eastern Tethys). Among a total of fifteen species of Discocyclina, Orbitoclypeus and Asterocyclina, six of them appear to be confined to Indian subcontinent while seven species are common both to the peri-Mediterranean/Europe region (Western Tethys) and Indian subcontinent. Two species, Asterocyclina sireli, a four-ribbed species of possibly Indo-Pacific origin, and Orbitoclypeus haynesi that form large populations in Fulra Limestone, appear to have spread into North Africa and Turkey but not into European platforms as a response to Middle Eocene Climatic Optimum (MECO). The lack of Lutetian and Priabonian fauna in the studied sections, either due to a hiatus or unsuitable depositional environments, hampers the establishment of the actual stratigraphic ranges of the identified taxa. Our record provides us to characterize the orthophragminids in shallow benthic zone (SBZ) 17 for Eastern Tethys in detail by comparing the data from the above localities with those from the North Africa, Europe and Turkey, showing the change in diversity.